Postoperative Serum Calcium as a marker for Hypocalcemia after Thyroidectomy - Muhammad Qasim Qazaal (Archivos Venezolanos de Farmacología y Terapéutica, 2021)
Objectives: The present study aimed to determine the incidence of hypocalcemia (temporary and permanent) following total thyroidectomy and to assess whether or not its clinical and biochemical features could be used as predictive markers for postoperative hypocalcemia.Methods: A total of 144 patients who undergone a total thyroidectomy were constitutes the base of such prospective study. Serum calcium were measured in addition to details of the operation including the pathology and complications were recorded. Results: The rate of hypocalcemia was identified in 70 patients (48.61%), among them, 62 patients (43.05%) were found to developed temporary hypocalcemia and only 8 patients (5.55) identified to developed a permanent hypocalcemia. Temporary hypocalcemia was significantly more common among patient who had a toxic goiter. The mean of serum calcium levels that measured at 6 hours and 24 hours postoperatively were significantly different among study’s groups of hypocalcemia (normo-calcemia, temporary and permanent hypocalcemia). Conclusion: The serum calcium levels that measured six hours and 24 hours post thyroidectomy are useful as predictive marker for developing hypocalcemia.